2020
DOI: 10.1038/s41401-020-00512-4
|View full text |Cite
|
Sign up to set email alerts
|

Waixenicin A, a marine-derived TRPM7 inhibitor: a promising CNS drug lead

Abstract: Ion channels are the third largest class of targets for therapeutic drugs. The pharmacology of ion channels is an important research area for identifying new treatment options for human diseases. The past decade or so has seen increasing interest in an ion channel protein belonging to the transient receptor potential (TRP) family, namely the melastatin subfamily member 7 (TRPM7), as an emerging drug target. TRPM7 is a bifunctional protein with a magnesium and calcium-conducting divalent ion channel fused with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…581 Waixenicin A, a xenicane diterpenoid originally isolated from Sarcothelia edmondsoni, demonstrates several pharmacological activities including neurite outgrowth and reduction of hypoxic-ischemic brain injury, all of which have been recently reviewed. 582 The structures and biological activities observed for over 200 sterols isolated from cnidarians has also been reviewed. 583 Twenty-seven new sterols were reported from so corals, including secosterols 1330 and 1331 (Clavularia ava), 546 two anti-inammatory secosterols 1332 and 1333 (Sinularia leptoclados), 584 1334 (Iciligorgia sp.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…581 Waixenicin A, a xenicane diterpenoid originally isolated from Sarcothelia edmondsoni, demonstrates several pharmacological activities including neurite outgrowth and reduction of hypoxic-ischemic brain injury, all of which have been recently reviewed. 582 The structures and biological activities observed for over 200 sterols isolated from cnidarians has also been reviewed. 583 Twenty-seven new sterols were reported from so corals, including secosterols 1330 and 1331 (Clavularia ava), 546 two anti-inammatory secosterols 1332 and 1333 (Sinularia leptoclados), 584 1334 (Iciligorgia sp.…”
Section: Reviewmentioning
confidence: 99%
“…581 Waixenicin A, a xenicane diterpenoid originally isolated from Sarcothelia edmondsoni , demonstrates several pharmacological activities including neurite outgrowth and reduction of hypoxic-ischemic brain injury, all of which have been recently reviewed. 582…”
Section: Cnidariansmentioning
confidence: 99%
“…In 1984, Scheuer and Clardy reported the isolation of waixenicin A ( 1 ) from an extract of the marine soft coral Sarcothelia edmondsoni harvested along the Hawaiian coast (Figure ). 1 stands out due to its unique biological profile and has been intensively investigated for its potential to act as a specific inhibitor of transient receptor potential melastatin 7 (TRPM7) channels, blocking cell proliferation with an Mg 2+ -dependent IC 50 value of 16 nM. Interestingly, 1 displayed no inhibitory activity for TRPM6, which represents the closest homologue of TRPM7 .…”
Section: Introductionmentioning
confidence: 99%
“…Sun and colleagues found that 19 could promote the growth of neural synapses in vitro, and reduced neonatal hypoxic-ischemic brain damage and improved long-term behavioral outcomes in mice, suggesting that 19 could be used as a tool molecule for selective inhibition of TRPM7 and an active lead compound for the treatment of TRPM7-related diseases. 91 Na + -Ca 2+ exchangers (NCX) agonists…”
Section: Acid-sensing Ion Channels (Asics) Inhibitorsmentioning
confidence: 99%